Applications of Computer Technologies in Teaching Applied Mechanics - Asraev Zafar Rizakulovich; Bibutov Narzullo Salimovich (Genius Journals, 2022)
The article describes the main scientific and methodological results of new computer methods obtained in the teaching of "Applied Mechanics". A methodology has been developed for solving the tasks set in teaching "Applied Mechanics" and "Strength of Materials" based on computer learning technologies.
Keywords: LabVIEW; COMSOL; Cisco Trace; Solidworks